PEMANFAATAN PENINGKATAN HASIL BELAJAR PADA SISTEM ELEKTRONIK POWER STEERING - Muhammad Setiawan Dwi Saputro; Ahmad Rozikin (Automotive Science and Education Journal, 2024)
This research aims to develop virtual demonstration media for a car power steering electronic overhaul simulation based on an Android mobile application, find out how appropriate the demonstration media is for learning effectiveness, and find out how well the user's understanding of the media used in the learning process increases.This research used development research methods with the ADDIE development model and product trials using a one-group pretest-posttest design which was tested on students at Semarang State University, majoring in engineering education, namely in the chassis system course with 30 respondents. The instruments used are questionnaires and tests. Material expert validity questionnaire and media expert validity questionnaire. For the test, 27 questions were used which had previously been tested for validity and reliability.The media validation results obtained a score of 174 out of 200 by material experts and a score of 170 out of 200 by media experts. The material expert's assessment reached 85.5% with the criteria "very feasible," while the media experts assessed 87.5% with the "very feasible" category. The learning media that has been created has been proven to have a positive impact on improving student learning outcomes. This can be seen from the difference in the average pre-test score of 33 and post- test of 80, increasing learning outcomes of 47. The t-count value is 31.85, while the t-table at the 5% significance level is 2.045. These data show that t-count > t-table so it can be concluded that there is a significant increase in learning outcomes between the pre-test and post-test results. The n-gain test results show an average value of 0.7026 with a high improvement category.Based on the research carried out, suggestions for continuous development are needed. The hope is that it can be conceptualized as a 3D simulation. It is hoped that the media will be expanded in compatibility and integrated with non-Android devices. It still requires further guidance and supervision from lecturers. For further research, it is recommended to use current development software compared to the currently used version of Unity 3D. The goal is that the learning media produced for Android applications can be better and more flexible than existing products.